Real-time biofeedback to control trunk power production in ergometer rowing - Pitto, L.; Simon, F.; Banet, L.; Ertel, G.; Mornieux, G. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The purpose of this study was to test a real-time feedback for ergometer rowing based on parameters describing a rower`s technique, specifically the curve of the power produced by the trunk. The goal was to enhance the trunk engagement during the drive phase. Eleven rowers performed an ergometer rowing session at 20spm and maximum intensity, where their habitual technique was measured. Then, they performed six sessions of 3min with feedback exposure on trunk time to peak power and work ratio. On average, rowers were able to advance their trunk power production within the drive phase by 1.3%, but without significant effect on performance, despite a mean 43W increase in trunk power. Feedbacks of this kind could be used in training to address specific parameters of a rower`s technique.